Evaluation of young Falcata plus-trees for veneer and plywood production in the Philippines - Jimenez, Juanito P., Jr (Philippine Journal of Science, 2022)
Young (3-, 5-, and 7-yr-old) falcata [Falcataria moluccana (Miq.) Barneby & J W. Grimes] trees were evaluated for their suitability to be processed into veneer and plywood. Three sample trees per age level were harvested from industrial tree plantations in Agusan del Norte and Surigao del Sur, Mindanao, Philippines. A straight portion of each tree from the bottom up to 4.5 m long was cut and divided into three billets at 1.5 m each. These were assigned to be peeled into 0.85-, 2.20-, and 2.80-mm veneer thicknesses. Veneering was done in a spindleless lathe using established lathe settings for falcata billets. Veneer quality per thickness and age level was evaluated based on the frequency and depth of lathe checks (LC). Results showed that LC occurred more frequently in the 2.20-mm-thick veneer, but these were shallower than the 2.80-mm, which had less frequent but deeper LC. On the other hand, age was found to significantly affect the formation of deeper LC in the 3-year-old 0.85-mm thick veneer; thus, it should only be used as a core veneer. The bond strength quality test showed that, regardless of age, falcata plywood passed the glue bond requirement of PNS ISO 12466-2:2016.